PEMBIASAAN SHALAT DHUHA UNTUK MENINGKATKAN DISIPLIN BELAJAR SISWA - Eni Sri Mulyani; Hunainah Hunainah (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2021)
The research objective was to describe the improvement of student learning discipline through habituation of Dhuha prayer at SD Negeri Kadingding, Kibin District. The data type of this research is descriptive qualitative using three data analyzes, namely data reduction, data presentation, and conclusion drawing. This study uses a qualitative descriptive approach which includes field research (Field Research) with data collection techniques namely observation, interviews, and documentation. The subjects of this study were students of SD Negeri Kadingding, Kibin District. Data were collected from 33 grade V students, 17 male students and 16 female students. Class V was taken as the sample because grade V children are in the high grade level between grades IV, V, VI. This research was conducted for 40 days starting from 23 July to 8 October 2019. The results of this study indicate 1) thatwith the implementation of the practice of the Dhuha prayer at SD Negeri Kadingding, Kibin District, which is held every Tuesday to Friday at 06.30 - 07.00, the Duha prayer is carried out in congregation starting from grade I to grade VI, the number of cycles of dhuha prayer from the school recommends a minimum of 2 cycles of prayer in advance to improve time discipline and get used to performing Duha prayers. 2) the percentage of the implementation of this Dhuha prayer habit has an effect on increasing student discipline in learning; 3) The condition of the place used for the Dhuha prayer is inadequate, because it uses the school yard field by laying out a mat, so it takes time to prepare for the Dhuha prayer.